Film Review: Jagun Jagun, Nigeria, 2023. Produced by Euphoria 360 Media. Netflix. 129 minutes, Yoruba (with English subtitles). No price reported. Directed by Tope Adebayo and Adebayo Tijani - Yemi Atanda (Yoruba Studies Review, 2023)
I intend to argue in this review that the Yoruba film Jagun Jagun represents the transition of the Yoruba Travelling Theatre into the big screen motion picture. It has been a remarkable transformation from stage crafts to filmic crafts, while still retaining the “family” involvement in the vibrant business innovations of the New Nollywood. Doing this focuses on configuring the interface between technology and entrepreneurship with its attendance use of traditional visual elements, songs, dance, imageries, metaphors and other Yoruba poetic renditions for aesthetic values. However, it is noted that the inappropriate mingling of both traditional and modern visual effects influenced by the Western postmodernist style in filmic framing, composition, sound, music and war combat mode. Generally, the film occludes the postcolonial thematic relevance in the modern political African leaders in their visionless Machiavellian ideology.